DEVELOPMENT AND OPTIMIZATION OF CARVEDILOL FORMULATION USING EXPERIMENTAL DESIGN - Predrag Sibinovic; Valentina Marinkovic; Radoslav Palic; Ivan Savic; Ivana Savic-Gajić; Dragan Milenovic; Rada Jankovic (Journal of Engineering & Processing Management, 2014)
The aim of this paper was to develop and optimize the carvedilol tablets formulation using the full factorial design. The content of binder (PVP K30), content of disintegrant (crospovidone) and main compression force were used as the independent variables. Tablets were prepared by wet granulation. The percentage of released carvedilol from prepared formulation after 10 minutes was defined as the response. It has been found that formulation with the low content of binding agents (4.8%), high content of disintegrant (4.5%) and compression force of 50 N has the best profile of drug. The optimal formulation was defined based on implementation of pharmaceuticaltechnological tests (testing strength, friability, disintegrating, contents of drug substance, drug release profiles). The stability of the optimal formulation with carvedilol was estimated using the aging tests.
Keywords: carvedilol; formulation; experimental design; dissolution profile